The river [compact disc, unabridged] - Paulsen, Gary (Listening Library, 1993)
Because of his success surviving alone in the wilderness for fifty-four days, fifteen-year-old Brian, profoundly changed by his time in the wild, is asked to undergo a similar experience to help scientists learn more about the psychology of survival.